Population age structure and conservation status of Ferula sinkiangensis (Apiaceae) in Xinjiang, China - Tianxing Liu; Qiumei Cao; Lei Yang; Zhaoping Yang; Wenjun Li (Oryx)
Ferula sinkiangensis K.M. Shen is a threatened medicinal plant endemic to Xinjiang, China, with a small population size and a narrow distribution range. We assessed the status of this species with respect to its population age structure, the level of threat and extinction risk. Only one population remains, in Yining County, Xinjiang. We conducted field surveys of the population in 2022 and 2023, counting 2,033 and 1,515 individuals, respectively, in 144 sample quadrats. We assessed the age structure of the population by counting the number of basal leaves of each individual. The frequency distribution had an inverted J-shape, indicative of a relatively stable age structure. However, the number of mature individuals was small, raising concerns about the risk of genetic drift and inbreeding. This species is also threatened by habitat destruction and inappropriate collection practices. We recommend that F. sinkiangensis is categorized as Critically Endangered on the IUCN Red List on the basis of criteria B2ab(iii), C2a(i) and D.